Alarm to Global Hunger Phenomenon and Food Squandering - Bidabad, Bijan (American International Journal of Social Science Research, 2019)
A quarter to one-third of food materials are wasted every year and about one-sixth of the people of the world, which is about one billion people, are facing malnutrition and about one-third of them are hungry. A hunger tsunami is forecasted for 9 billion people of the world in 2050. Therefore, in order to gain victory on this crisis in 2050, the rules and the socio-economic framework should be changed to prevent the imbalanced distribution of agricultural products.